Enhanced Electrochemical Performance of Vanadium Redox Flow Batteries Using Li4Ti5O12/TiO2 Nanocomposite‐Modified Graphite Felt Electrodes - Zih‐Jhong Huang; Daniel Manaye Kabtamu; Aknachew Mebreku Demeku; Guan‐Cheng Chen; Ning‐Yih Hsu; Hung‐Hsien Ku; Yao‐Ming Wang; Tai‐Chin Chiang; Chen‐Hao Wang (ChemElectroChem)
Abstract In this study, Li4Ti5O12 (LTO) and TiO2 nanocomposites uniformly were synthesized on the heat‐treated graphite felt through (HGF) hydrothermal and heat treatment methods, denoted by LTO/TiO2@HGF, which LTO/TiO2@HGF acts as effective electrocatalysts to enhance the electrochemical activity in vanadium redox flow battery (VRFB) systems. The cyclic voltammetry (CV) curves of the LTO/TiO2@HGF show higher peak current densities and smaller peak separation than TiO2@HGF, HGF, and pristine graphite felt (PGF) for catalyzing V2+/V3+ and VO₂+/VO2+, indicating superior electrochemical activity of LTO/TiO2@HGF. The VRFB using LTO/TiO2@HGF as the positive and negative electrodes demonstrates an energy efficiency of 82.89 % at 80 mA cm−2. When the VRFB using LTO/TiO2@HGF is applied by a high current density of 200 mA cm−2, it still shows an energy efficiency of 62.22 %. However, the VRFB using PGF cannot perform any performance, and the VRFB using HGF only performs 51.94 %. This improvement can be attributed to the uniform distribution of LTO/TiO2 nanowires on the surface of the graphite felt and the presence of oxygen vacancies on LTO/TiO2, which increased the number of active sites for vanadium ion absorption.